Associations between the Neutrophil-to-Lymphocyte Ratio and Diabetic Complications in Adults with Diabetes: A Cross-Sectional Study - Wan, Heng (J Diabetes Res, 2020)
OBJECTIVE: The neutrophil-to-lymphocyte ratio (NLR) is an inexpensive and easily measurable laboratory index indicating systemic inflammation, while the application of many other inflammatory markers has been limited in daily clinical practice. However, large population studies about investigating the associations of the NLR level with diabetic complications including cardiovascular and cerebrovascular diseases (CVD), diabetic kidney disease (DKD), and diabetic retinopathy (DR) in the same population were limited. The aim of our study is to evaluate the associations between the NLR level and the prevalence of CVD, DKD, and DR in adults with diabetes simultaneously. METHODS: A cross-sectional survey of 4,813 diabetic adults was conducted in seven communities in China. Persons underwent several medical examinations, including the measurement of anthropometric factors, blood pressure, routinely analyzed leukocyte characteristics, glucose, lipid profiles, urine albumin/creatinine ratio, and fundus photographs. RESULTS: Compared with the first quartile of the NLR level, the odds of having CVD was significantly increased by 21% for participants in the highest quartile (OR 1.21; 95% CI 1.00, 1.47) (P for trend < 0.05). Similarly, the prevalence of DKD among participants in the highest quartile of the NLR level was significantly increased by 150% (OR 2.50; 95% CI 1.95, 3.19) (P for trend < 0.05). However, no association was found between the NLR level and the prevalence of DR (P for trend > 0.05). These associations were all fully adjusted. CONCLUSIONS: A higher NLR level was associated with an increased prevalence of CVD and DKD, other than DR, in diabetic adults.